The Effect Of Counseling On Decision Making In The Selection Of Equipment Iud Contraception In Accepters KB At The Mandrehe Health Center North in 2022 - Mestika Rija Helti; Niasty Lasmy Zaen (Jurnal EduHealth, 2023)
Indonesia is one of the most populous countries in the world. This population explosion occurred because of the very high rate of population growth. The government provides a series of efforts to suppress the rate of population growth so that a larger population explosion does not occur. One way that the government does is to promote family planning programs. The purpose of this study was to determine the effect of counseling on decision making in the selection of IUD contraceptives for family planning acceptors at the North Mandrehe Health Center. This type of research uses a pre-experimental design approach with one-group pretest-posttest design. The population in this study were all EFA mothers who visited the Puskesmas in the working area of the North Mandrehe Health Center, namely Hilimayo Village, as many as 84 people with the sampling technique of acidental sampling, a sample of 26 people was obtained. Bivariate data analysis used the Wilcoxon signed rank test. The results of this study indicate that the mean value of each is 0.00 (Pre) and 24 (Post). The results of statistical tests using the Wilcoxon test are known that the p value (0.000) < (0.05) means that Ho is rejected. The conclusion of the study is that there is a significant influence of counseling with decision making in the selection of IUD contraceptives on family planning acceptors at the North Mandrehe Health Center in 2022. It is recommended for midwives to improve the quality of counseling provided, especially related to politeness, simplicity of language and affirmation of all counseling materials, because These three things have the strongest impact on understanding so that they also affect the stability of the acceptor.